11x+13=15x-3

Simple and best practice solution for 11x+13=15x-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11x+13=15x-3 equation:


Simplifying
11x + 13 = 15x + -3

Reorder the terms:
13 + 11x = 15x + -3

Reorder the terms:
13 + 11x = -3 + 15x

Solving
13 + 11x = -3 + 15x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-15x' to each side of the equation.
13 + 11x + -15x = -3 + 15x + -15x

Combine like terms: 11x + -15x = -4x
13 + -4x = -3 + 15x + -15x

Combine like terms: 15x + -15x = 0
13 + -4x = -3 + 0
13 + -4x = -3

Add '-13' to each side of the equation.
13 + -13 + -4x = -3 + -13

Combine like terms: 13 + -13 = 0
0 + -4x = -3 + -13
-4x = -3 + -13

Combine like terms: -3 + -13 = -16
-4x = -16

Divide each side by '-4'.
x = 4

Simplifying
x = 4

See similar equations:

| -0.45=0.03x+.015 | | 0.3x+4.3=0.2x+1.2 | | 140+10x=462-6x | | -10=-7-3p | | 3x-6=8x+19 | | 15x-2x=9 | | P=i(24)-i^2(1.5) | | 4.5s-3.5t=19 | | w+0.16w=6.38 | | 9.8=x+8.9 | | 6.666x-7=0.25x-2 | | 13+15+18+1= | | 873-8= | | (7a+5t)(7a-5t)= | | 5x-1=7x+2 | | 7+2a-3=-9 | | 215=90+(10+8) | | 10x+9=11x | | 6.66666666666666666666666666666666666666666666666x-7=0.25x-2 | | 2-x=x+1 | | e=290+.07(1310) | | a+5.8=34.8 | | =90+(10+8) | | 18=8+2m | | (x-1)x(x+1)=1320 | | 60.00+42.95=57.95 | | 0.20x+0.05(6-x)=0.10(30) | | a(5)+b(-9)=c | | 7x-8=-8+5 | | 3x+17=-10 | | -2(x-5)+10=10 | | -(-3a+1)=3a-1 |

Equations solver categories